2011
DOI: 10.5897/ajmr10.359
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic activity of angiotensin antagonists

Abstract: Angiotensin Receptor Antagonists (ARAs) are widely used compounds in various cardiovascular disorders like Hypertension, Stroke prophylaxis, Heart failure. In addition, they are approved for the treatment of Diabetic Nephropathy. It is reported to produce analgesia on intracerebro-ventricular administration that could be blocked by naloxone. Angiotensin II has been reported for its pronociceptive activity. Angiotensin receptor antagonists block the action of angiotensin II by inhibiting its binding with its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The time taken for the animal to remove it tail out of the water was recorded. [15] Dosing schedule All the drugs are given according to their body weight once before starting the test.…”
Section: Tail Clip Testmentioning
confidence: 99%
“…The time taken for the animal to remove it tail out of the water was recorded. [15] Dosing schedule All the drugs are given according to their body weight once before starting the test.…”
Section: Tail Clip Testmentioning
confidence: 99%
“…Telmisartan could exert central analgesic effect as angiotensin receptor antagonists may modulate the analgesic action by increasing the pain threshold or by central mechanism by altering the pain modulating neurotransmitter level and activation of AT1 receptor with AngII also increases Ca ++ influx: their blockade leads to analgesic activity. 12 Also Wang JF et. al reported that ARAs produce analgesia on intracerebro-ventricular administration in rats and this action can be blocked by naloxone.…”
Section: Results: Tail Flick Methodmentioning
confidence: 98%
“…Intraperitoneal injection of acetic acid produces pain through activation of chemosensitive nociceptors 20 or irritation of the visceral surface, which lead to the liberation of histamine, bradykinin, prostaglandins and serotonin. 24 Also, it has been noted that the level of analgesia in acetic acid-induced models is indicated by the percent reduction in the number of abdominal constrictions.…”
Section: Discussionmentioning
confidence: 99%